MECHANISMS FOR DEVELOPING CREATIVE COMPETENCES IN THE MODERN EDUCATIONAL PROCESS (Universal International Scientific Journal, 2026)
This article analyzes the theoretical and pedagogical foundations of the development of creative competencies in students and pupils in the modern educational process. The study covers the concept of creative competence, its structural elements, the effectiveness of pedagogical strategies and innovative methods, as well as practical recommendations. The article shows systematic mechanisms aimed at the formation and strengthening of creative competencies in the educational process
Keywords: Creative competence; educational process; pedagogical strategy